ANALISIS SWOT: PROBLEM KANTOR KONSULTAN PAJAK X KABUPATEN LAMONGAN - Qosim Qosim; Sri Yaumi; Tri Winarsih; Rahma Jariatul (STIE Mahardhika, 2023)
This study aims to analyze the strengths, weaknesses, opportunities, and strategies that should be applied by Tax Consultants X during the Covid-19 pandemic. This research was conducted at the Tax Consultant Office in East Java and used a qualitative research method, with data collection techniques using interviews, questionnaires, observation and documentation. The data validation technique used is source triangulation technique and method triangulation. The results of this study indicate that the condition of the Tax Consultant Office X is declared good. Where the internal condition of the Tax Consultant Office X is 2.96 with the total strength factor obtained is 2.25, while the total weakness factor is 0.791. While the external factor of the Tax Consultant Firm X is 2.25 with the total opportunity factor obtained is 1.47, while the total of the threat factor is 0.787. When viewed from the results of the identification of internal and external factors of the Tax Consulting Office X, it shows that for now the most appropriate strategy is the SO Strategy. In the future, the X Tax Consultant can improve service facilities, expand the network to clients, create a website and carry out promotions using e-WOM.